The Effect of the Puzzle-Media-Assisted Problem-Based Learning Model on the Science Learning Activity of Class V Students - Muslimin, Muslimin; Krismanto, Wawan; Khaeriyah, Ummul (Institute Of Advanced Knowledge and Science, 2025)
This study aims to analyze the influence of the problem-based learning model (PBL) supported by puzzle media on the learning activity of students in science subjects in class V UPT SD Negeri 3 Otting, Sidrap Regency. The research method used was a quantitative experiment with a one-group pretest-posttest design. Data collection was carried out through observation sheets assessed by observers, then analyzed using descriptive and inferential statistics with a paired sample t-test. The results of the study show that the application of the Problem-Based Learning (PBL) model assisted by puzzle media can significantly increase students' learning activity. Learners become more active in asking questions, participating in group discussions, as well as showing improvements in problem-solving skills. With interesting and interactive problem-based learning, students are more motivated to understand the material and more courageous in expressing opinions. Therefore, the use of the Problem-Based Learning (PBL) model assisted by puzzle media is recommended as an effective learning strategy in increasing the learning activity of students in elementary school.